1990
DOI: 10.1111/j.1502-3931.1990.tb01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic change of distributional patterns of pore systems in Cythere species and its phylogenetic significance

Abstract: Species of Cythere (Ostracoda, Crustacea) have about one hundred normal pore systems on each valve of the carapace. These can be classified into five types on the basis of morphological features. They were examined in the light of intraspecific variation and interspecific difference. Each of the five pore systems has its own mode of ontogenetic increase in number. Comparison among fourteen Cythere species shows that the distributional patterns are completely identical in the A‐3 stage, but that they are classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…The phylogenetic reconstruction of Ostracoda by the analysis of the carapace pore-systems (i.e., a pore with a bristle) was first proposed and exemplified by Tsukagoshi (1990). He examined 14 Cythere species, and concluded that the interspecific differentiation in distributional patterns of poresystems on the carapace for later instars (A-2, A-1 and adult) reflected the phylogeny of the genus Cythere.…”
Section: Introductionmentioning
confidence: 98%
“…The phylogenetic reconstruction of Ostracoda by the analysis of the carapace pore-systems (i.e., a pore with a bristle) was first proposed and exemplified by Tsukagoshi (1990). He examined 14 Cythere species, and concluded that the interspecific differentiation in distributional patterns of poresystems on the carapace for later instars (A-2, A-1 and adult) reflected the phylogeny of the genus Cythere.…”
Section: Introductionmentioning
confidence: 98%
“…His work was followed by [26] [62][63][64] for species of other genera. This method of phylogenetic reconstruction, proposed by [21], was termed 'differentiation of distributional pattern of pore (DDP) analysis' [61]. The pore distribution in L. kamiyai was examined by this method [16], and the results were compared to the pore data of 17 other Loxoconcha species (Figure 16).…”
Section: Hingement Morphology and Dimorphismmentioning
confidence: 99%
“…The number, distribution, and differentiation of pores on the ostracod carapace surface during ontogeny have been studied to determine phylogenetic relationships among species [61]. The reconstruction of ostracod phylogeny based on pore analyses was first proposed by [21] for 14 species of the genus Cythere. His work was followed by [26] [62][63][64] for species of other genera.…”
Section: Hingement Morphology and Dimorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…These extend from the valve surface through pore canals, and are serviced by dendrites within the noncalci¢ed inner lamella of the carapace (Tsukagoshi 1990). Apart from marginal pore canals, the remaining normal pore canals are distributed over the entire carapace surface.…”
Section: Introductionmentioning
confidence: 99%